Using Google Word Coach Game to Enhance Students’ Vocabulary Mastery - suryadi, Suryadi (Cakrawala: Jurnal Pendidikan, 2022)
The research was conducted with the aim of knowing the use of the Google Word Coach game in helping students improve vocabulary skills. The research method uses Quasi Experimental Design with Nonequivalent Control Group Design by comparing student learning outcomes between the experimental class and the control class. In achieving this goal, the Pre and Post Group (PPG) is used. The pre and post design (PPG) was applied at Madrasah Aliyah Negeri I Serang, the research population was 270 students in class XI science and the research sample was 80 students. Sampling was done by snoballing sampling technique. The data analysis technique used the T test. The results showed that the observed T value was 7.313 and the Sig value was 0.00 <0.05. So it can be concluded that by using the Google Word Coach game students are able to improve their mastery of English vocabulary. The use of digital media and the latest technology by students in their English learning materials should be studied more by researchers in the future.